The Effects of Education Program on the Nursing Practice Guideline for Preventing Ventilator Associated Pneumonia and Incidence Rates of Ventilator Associated Pneumonia in Surgical Wards at Phra Nakhon Si Ayutthaya Hospital. - ชาญชะโรจน์ รวงทอง (Journal of Preventive Medicine Association of Thailand, 2019)
This Study is a quasi-experimental research, one group pre-post test design type, the objective of this study is to compare mean score of nursing practice guideline for preventing ventilator associated pneumonia (VAP) and incidence rates of vap on pre-post education program, The total number of study population, is 36 register nurses who work at male / female surgical wards at Phra Nakhon Si Ayutthaya hospital, a total 94 patients used ventilators at male / female surgical wards at Phra Nakhon Si Ayutthaya hospital from January-August 2015. 94 patients sampling population were devided according to the specified qualities. The data collecting instrument were the assessment form on the education program by the questionnaire, nursing practice guideline for vap prevention (2014) and vap record form of Phra Nakhon Si Ayutthaya hospital respectively. The assessment nursing practice guideline for vap prevention form had 0.71 reliability values. The data analysis was excuted by the statistics of number, percentage, average, standard deviation, Chi-square and Dependent t-test. The results show that the mean score of nursing practice guideline for vap prevention in post test is higher than pretest were significant (p<.001) and incidence rate of vap in post test is lower than pretest were significant (p=.005). Therefore, this education program should be useful for sustainable develoment in education program and nursing practice guideline for preventing in the other wards